IDENTIFIKASI TATA KELOLA TI PADA PROSES MENINGKATKAN ORIENTASI PELANGGAN DAN TINGKAT LAYANAN BERDASARKAN COBIT 4.1 STUDI KASUS : STMIK KHARISMA MAKASSAR - Luigi Fabio Giofany; Irfan A Palalloi; Arfan Yunus (JTRISTE, 2015)
This research carried out with regard to the implementation of IT Governance to the process of improve customer orientation and service levels in STMIK Kharisma. The purpose of this study was to produce current conditions, the level of maturity of IT Governance in STMIK Kharisma, and produce recommendations for improve of IT Governance processes improve customer orientation and service level by using CobIT 4.1. CobIT 4.1 is one of the IT governance standards could be tailored the needs STMIK Kharisma to performe and asses their IT implementation. Data collected by Interview technique to determine the business goals and IT goals in STMIK Kharisma , as well as to determine the maturity level of IT Governance with the questionnaitr technique. After going through testing the validity and reliability, the questionnaire stated reliable with Alpha Cronbach value greater than 0,6, and declared valid if Alpha Cronbach value greater than 0,708. The results of this study indicate the level of maturity of as-is conditions there is at level 1 ( the attribute SE ) and are at level 2 (on the attributes of AC, PPP, TA, RA, and GSM ), while the expected conditions STMIK Kharisma at the level of 4 (Managed and Measurable), then analysis the level of the gap, and will produce recommendations for improvements to the mapping of each attribute to be achieved in activities that support the implementation of expected conditions (to-be) intitution. Where at level 2 ( Repeatable but Intuitive) focused on planning, on level 3 (defined) focuses on identification and implementation, and on level 4 (Managed and Measurable) focuses on the repair, maintenance, monitoring, and documentation of services already in STMIK Kharisma.